PALAEOSEISMOLOGICAL INVESTIGATION OF THE GYRTONI FAULT (THESSALY, CENTRAL GREECE) - Tsodoulos, I.; Chatzipetros, A.; Koukouvelas, I.; Caputo, R.; Pavlides, S.; Stamoulis, K.; Gallousi, C.; Papachristodoulou, C.; Ioannides, K.; Belesis, A.; Kremastas, E.; Kalyvas, D. (Bulletin of the Geological Society of Greece, 2016)
Two paleoseismological trenches were excavated across the Gyrtoni Fault in NE Thessaly and studied in order to understand the recent seismotectonic behavior of this structure. Twenty five fluvial-colluvial sediment and pottery samples from both the upthrown and the downthrown fault blocks were investigated. Optically Stimulated Luminescence (OSL) dating has been applied to date both sedimentary depositspalaeosoils and pottery fragments. Paleoseismological analysis of the two trenches indicates evidence of three surface faulting events in the time span between 1.42 ±0.06 ka and 5.59 ± 0.13 ka. The observed vertical displacement per event of 0.50 m corresponds to an Mw 6.5 ± 0.1 earthquake. An average fault slip rate of 0.41 ± 0.01 mm/yr and an average recurrence of 1.39 ± 0.14 ka for earthquakes were estimated. The results documented the activity of the fault and since the return period from the most recent event (minimum age 1.42 ± 0.06 ka) has expired, the possibility for reactivation of this active structure in the near future should be included in Seismic Hazard Assessment.